How Much Knowledge of Derived Words Is Needed for Reading?. (21st November 2019) - Laufer, Batia; Cobb, Tom
Abstract: The study explores the usefulness of the word family as the unit of counting in studies of lexical coverage and comprehension. It determines the proportion of texts covered by the various members of a word family, that is, basewords, inflected words, and derived words, and analyzes the contribution of the affixed words to lexical thresholds. This exploration was performed by a text analysis computer program called Morpholex that analyzes the entire lexis of an entered text, pulling out all words bearing prefixes and suffixes and counting the unaffixed words as basewords. We analyzed a variety of texts, academic and narrative, authentic and simplified, and calculated the number and percentage of basewords and affixes in each text. We also located the most frequent affixes in our text corpus and demonstrated which affixes and how many contributed to 95 per cent and 98 per cent text coverages. Our results show that reaching the lexical thresholds for reading does not require the knowledge of most of the derived words in a word family since a small number of frequent affixes will provide the necessary coverage together with the basewords and inflections.